Pattern of client patron relationship between collectors and fisherman in Jantur Baru Village, Muara Muntai District, Kutai Kartanegara Regency - Wahyudi Wahyudi; Qoriah Saleha; Erwiantono Erwiantono (Jurnal Ilmu Perikanan Tropis Nusantara (Nusantara Tropical Fisheries Science Journal), 2024)
The purpose of this study was to determine the pattern of patron-client relationships with fishermen and collectors in Jantur Baru Village and to find out the problems encountered in patron-client relationships with fishermen and collectors in Jantur Baru Village. The pattern of the patron-client relationship in Jantur Baru Village is a general pattern of reciprocity in which the employment relationship agreement made by the patron and the client does not set a time limit for the return of capital provided by the patron, in this case the patron to the client, in this case fishermen. The problems encountered in the patron-client relationship in Jantur Baru Village are found in two perspectives. The problem from the point of view of collectors (patrons) is that there are fishermen who secretly sell their catch to other collectors and the problem from the point of view of fishermen (clients) is that the purchase price set by the collectors is deemed inappropriate by fishermen.